Persistence of Parent-Reported ADHD Symptoms From Childhood Through Adolescence in a Community Sample. (January 2016) - Holbrook, Joseph R.; Cuffe, Steven P.; Cai, Bo; Visser, Susanna N.; Forthofer, Melinda S.; Bottai, Matteo; Ortaglia, Andrew; McKeown, Robert E.
Objective: To examine ADHD symptom persistence and factors associated with elevated symptom counts in a diverse, longitudinal community-based sample.Method: Parents reported demographics and completed a diagnostic interview repeatedly over a 6-year period. At Time 1, 481 interviews were completed about children (5-13 years); all participants were invited to four annual follow-up interviews, and 379 (79%) completed at least one. Inattentive (IA) and hyperactive-impulsive (HI) symptom counts were modeled with logistic quantile regression, while accounting for study design complexities.Results: The prevalence of seven IA symptoms remained stable from early childhood through late adolescence. The prevalence of eight HI symptoms decreased by more than half over time. After demographic adjustment, the upper quartile of HI symptom counts decreased with age ( p < .01). High HI symptom counts persisted more among those with high IA symptom counts ( p = .05).Conclusion: This study further characterizes and provides insights into ADHD symptom trajectory through adolescence.